PEMIKIRAN MAHABBAH DALAM PERSPEKTIF SYEIKH AHMAD SHOHIBULWAFA TAJUL ‘ARIFIN (ABAH ANOM) - Hilmi, Akhmad Robittul (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2023)
Abah Anom, a prominent Sufi figure in Indonesia, is acknowledged as the spiritual leader (murshid) of the Qadiriyyah wa Naqsabandiyyah order (TQN). His teachings primarily revolve around the practice of "zikir" but also encompass broader aspects. This is evident in the pre-zikir prayer: "ilaahī anta maqṣūdī wa riḍāka maṭlūbī a’ṭinī maḥabbataka wa ma’rifataka" emphasizing the significance of "mahabbah" or love as a central theme consistently integrated into every aspect of his Sufi practice. What were Mahabbah's perceptions of Abah Anom's Sufi teachings? To what extent was this "mahabbah" expressed? How does "mahabbah" correlate with "zikir"? Using library research and a qualitative approach, the study involved descriptive analysis, focusing on various dimensions of Mahabbah, including love for humanity, wealth, position, and, importantly, love for Allah. Abah Anom expounded clearly on the relationship between "mahabbah" and "zikir," often using simple analogies to illustrate their correlation. In summary, Abah Anom extensively discussed the concept of "mahabbah" within his Sufi teachings, integrating it as a prominent theme through interjections and comprehensive discussions. He also elucidated the interconnection between "mahabbah" and "zikir" frequently using straightforward analogies to underscore their correlation.